2022
DOI: 10.1172/jci.insight.160909
|View full text |Cite
|
Sign up to set email alerts
|

Human T-bet+ B cell development is associated with BTK activity and suppressed by evobrutinib

Abstract: Recent clinical trials have shown promising results for the next-generation Bruton’s tyrosine kinase (BTK) inhibitor evobrutinib in the treatment of multiple sclerosis (MS). BTK has a central role in signaling pathways that govern the development of B cells. Whether and how BTK activity shapes B cells as key drivers of MS is currently unclear. Compared with levels of BTK protein, we found higher levels of phospho-BTK in ex vivo blood memory B cells from patients with relapsing-remitting MS and secondary progre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 56 publications
0
16
0
Order By: Relevance
“…59 BTK inhibition by Evobrutinib impaired the ability of CXCR3+B cells to penetrate through human brain endothelial layers. 60 The Immune-Related Mechanisms of BTK Inhibition in the Central Nervous System Targeting B Cell As mentioned above, BTK is a vital component of BCR signaling regulating B-cell functions. Targeting BTK has been widely studied and applied in the treatment of multiple sclerosis (MS).…”
Section: Beyond Bcr Signaling Pathwaymentioning
confidence: 99%
See 4 more Smart Citations
“…59 BTK inhibition by Evobrutinib impaired the ability of CXCR3+B cells to penetrate through human brain endothelial layers. 60 The Immune-Related Mechanisms of BTK Inhibition in the Central Nervous System Targeting B Cell As mentioned above, BTK is a vital component of BCR signaling regulating B-cell functions. Targeting BTK has been widely studied and applied in the treatment of multiple sclerosis (MS).…”
Section: Beyond Bcr Signaling Pathwaymentioning
confidence: 99%
“…Evobrutinib also prevented memory B cell migration across the brain endothelial layer and maturation into ASCs, which can be considered a promising therapeutic approach to attenuate local antibody production in MS patients. 60 A recent study shed new light on the regulatory function of BTKi on B cells in MS. Li et al 69 reported that the treatment of BTKi could inhibit mitochondrial respiration in human B cells in vitro, resulting in an anti-inflammatory shift in B cell properties. The expression of costimulatory molecules is reduced in B cells, limiting their function as antigen-presenting cells to activate pathogenic T cells.…”
Section: Dovepressmentioning
confidence: 99%
See 3 more Smart Citations